2015
DOI: 10.1039/c5ce01366f
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide diphosphonates based on a V-shaped ligand: syntheses, structures, experimental and theoretical luminescence properties

Abstract: One series of isostructural lanthanide phosphonates, namely [Ln 2 IJH 2 L) 3 ]ij(H 2 O) 5 ] (H 4 L = (5-methyl-1,3-phenylene)bisIJphosphonic acid); Ln = Eu (1), Gd (2), Tb (3), and Dy (4)), have been successfully synthesized from a V-shaped rigid ligand. Systematic characterizations using single-crystal and powder X-ray diffraction (XRD), thermogravimetric analyses (TGA), and photoluminescence spectroscopy were accomplished. It was found that these compounds all crystallize in the cubic I2 1 3 space group, showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…81 In three Tb 3+ complexes, the triplet energy level T 1 of ligand H 4 L 3 (21552 cm −1 ) is extremely close to the resonant level of Tb 3+ ion (20500 cm −1 ) in complex 13, and the energy gap (1052 cm −1 ) is too small to prevent the back energy transfer from excited state of Tb 3+ ion to triplet state of the ligand. 82,83 Therefore, a relatively lower efficiency of ligand-to-metal energy transfer takes place in complex 13, leading to a low observed luminescence quantum yield of complex 13. Likewise, it is not difficult to understand that, in the Eu 3+ complexes, the observed luminescence quantum yields of complexes 2 and 6 (10.1% and 14.3%) are higher than that of complex 11 (4.8%), since the triplet state of the ligand H 4 L 3 (21552 cm −1 ) is very close to the 5 D 2 emitting state of Eu 3+ ion (212000 cm −1 ), which offers the opportunity for the thermalassisted back energy transfer from excited state of central Eu 3+ ion in complex 11.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…81 In three Tb 3+ complexes, the triplet energy level T 1 of ligand H 4 L 3 (21552 cm −1 ) is extremely close to the resonant level of Tb 3+ ion (20500 cm −1 ) in complex 13, and the energy gap (1052 cm −1 ) is too small to prevent the back energy transfer from excited state of Tb 3+ ion to triplet state of the ligand. 82,83 Therefore, a relatively lower efficiency of ligand-to-metal energy transfer takes place in complex 13, leading to a low observed luminescence quantum yield of complex 13. Likewise, it is not difficult to understand that, in the Eu 3+ complexes, the observed luminescence quantum yields of complexes 2 and 6 (10.1% and 14.3%) are higher than that of complex 11 (4.8%), since the triplet state of the ligand H 4 L 3 (21552 cm −1 ) is very close to the 5 D 2 emitting state of Eu 3+ ion (212000 cm −1 ), which offers the opportunity for the thermalassisted back energy transfer from excited state of central Eu 3+ ion in complex 11.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The first diffraction peak of PAS-Hf (2 : 1 : 0.5) represented the formation of the interlayer by the coordination of the -PO 3 groups and Hf. 34 The 31 P MAS NMR spectrum in Fig. 1E shows the two different binding modes of phosphonates.…”
Section: Catalyst Characterizationmentioning
confidence: 98%
“…The synthesis of (5-methyl-1,3-phenylene)bis( phosphonic acid) (H 4 L) has been reported in our recent work. 6 Elemental analyses were performed on a Vario EL III elemental analyzer. IR spectra were recorded in the range of 4000-400 cm −1 on a Nicolet 6700 FTIR spectrometer with KBr pellets.…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…Our results revealed that the crystallinity of metal diphosphonates could also be improved by the introduction of one methyl group on the benzene core. With this method employed, four lanthanide 6 and six transition metal diphosphonates with a variety of structures have been obtained from H 4 L. There are not only many π⋯π interactions but also many C-H⋯O and C-H⋯π interactions in these structures, suggesting the contribution of weak interactions to the improved crystallinity.…”
Section: The Role Of Weak Interactions In the Species Formationmentioning
confidence: 99%
See 1 more Smart Citation